Approaches to the Middle Paleolithic rockshelter and cave research in Croatia - Karavanić, Ivor (Array, 2006)
There is a long tradition of cave and rockshelter research in Croatia. The first Middle Paleolithic site to be discovered was Krapina, located in northwestern Croatia. It was excavated by Dragutin Gorjanović-Kramberger. His excavation methodology was very progressive for the time, and included excavation with respect to the stratigraphic sequence and notes on the horizontal distribution of finds at certain parts of the site. In southern Croatia, the only systematically excavated Middle Paleolithic site is Mujina Pećina. The three-dimensional recording of all artifacts and ecofacts enabled the spatial patterning. This paper presents spatial analysis of certain occupation levels from Mujina Pećina, which provided the reconstruction of some aspects of behaviour of the Mousterian people on the eastern Adriatic coast.